The effect of oral habits in the oral cavity of children and its treatment - Gartika, Meirina (Padjadjaran Journal of Dentistry, 2008)
Oral habits include habit which is continuously done and has the potential to cause defects in teeth and perioral tissues. Some of the oral habits are finger/thumb sucking, lip sucking/biting, nail biting, bruxism, abnormal swallowing and mouth breathing. The etiology of oral habits includes the disharmonious relationship between parents and children, dissatisfaction in oral phase, premature weaning, emotional disturbance, anomaly, and diseases. Oral habits will influence the development of occlusion and perioral structures in children in the growing and development process. The treatment of oral habits can be done with or without appliances. The non-appliance treatment consists of psychological approach, medical approach and myofunctional therapy while the appliance treatment will include the use of orthodontic appliances.